Bone remodeling at the endocortical surface of the human femoral neck: a mechanism for regional cortical thinning in cases of hip fracture. - Power, J; Loveridge, N; Lyon, A; Rushton, N; Parker, M; Reeve, J (2003)
Endocortical remodeling and wall thickness (W.Th.) were measured in femoral neck bone from 12 female fracture cases (81.3 +/- 1.5 years) and 12 sex-matched controls (81.9 +/- 1.9 years). Regionally, osteoid and eroded surface were increased, whereas W.Th. was reduced. These processes likely contribute to cortical bone loss seen in hip fracture. INTRODUCTION: Because periosteal expression of alkaline phosphatase was similar between cases and controls, we hypothesized that the mechanism causing the marked femoral neck cortical thinning associated with hip fracture may be net endocortical bone loss. METHODS: Twelve female cases of femoral neck fracture (mean age = 81.3 +/- 1.5 years) and 12 age- and sex-matched postmortem controls (mean age = 81.9 +/- 1.9 years) were included in the study. Samples of their femoral neck bone were embedded in methyl methacrylate, sectioned at 10 microm, and stained with Solochrome cyanine R and Goldner's trichrome for the detection of osteoid (%OS/BS) and resorption surfaces (%ES/BS) respectively. In addition, wall thickness (W.Th.) and lamellar thickness (Lm.Th.) data were also collected from identifiable endocortical bone packets as a measure of formative potential. RESULTS AND CONCLUSIONS: %OS/BS was significantly elevated in the anterior (control = 3.4 +/- 0.7: fracture = 11.0 +/- 2.3; p = 0.0001), inferior (3.4 +/- 1.0: 9.9 +/- 3.0; p = 0.0009), and posterior quadrants (3.2 +/- 0.8: 9.1 +/- 2.3; p = 0.0021). Only for anterior region was increased %ES/BS demonstrated in the fracture group (2.8 +/- 0.6: 5.3 +/- 0.7; p = 0.055). W.Th. (mm) was reduced only in the inferior region of the fracture cases (control = 33.7 +/- 1.2: fracture = 30.6 +/- 0.9; p = 0.013), whereas Lm.Th. was also reduced inferiorly (control = 2.7 +/- 0.08: fracture = 2.5 +/- 0.08; p = 0.042). These data suggest that an endocortical remodeling imbalance involving reduced bone formation within inferior region coupled with elevated anterior resorption may make an important contribution to the cortical thinning observed in cases of femoral neck fracture.